The study of the correlation between productivity and biochemical parameters of soybean - A. R. Ashiev; K. N. Khabibullin; M. V. Skulova (Зерновое хозяйство России)
The purpose of the current study was to identify the correlation between seed productivity and quality indicators of the soybean collection samples. The study was carried out in the fields of the FSBSI “ARC “Donskoy” in 2019–2021. Over the years of study, the weather conditions were unstable and differed from the long-term mean data. The objects of research were 85 soybean samples from the world collection of the N. I. Vavilov Institute. The study has established that the most variable trait was productivity (V = 45.4 %) than protein (V = 6.4 %) and oil percentage in seeds (V = 9.7 %). The correlation between productivity and seed quality was weak and amounted to r = –0.24 with protein and r = 0.29 with oil content. The correlation between protein and oil content was higher and amounted to r = –0.51. Span charting showed that the bulk of soybean collection samples had a mean protein percentage of 40.5–43.0 %, and the most productive samples had 39.0–39.5 % of protein. The predominant part of the collection had an oil content in seeds from 19.0 to 21.5 %, which also included samples with maximum seed productivity and 19.0–19.5 % of oil. Against the background of the established negative correlation between protein and oil content in seeds, there were found the samples with a very high content of protein and oil in seeds at the same time. There were selected three soybean collection samples (‘Zodiak’ (Moldova), ‘Selekta-101’ (Russia) and ‘Antuxiaoneidou’ (China), which had large productivity a high content of protein and oil in seeds. The study results of the correlation between seed productivity and quality indicators of the soybean collection samples will be used in further breeding work.